Optoelectronic properties of electron beam-deposited NiOx thin films for solar cell application - Hasan A.K.M.; Sobayel K.; Raifuku I.; Ishikawa Y.; Shahiduzzaman M.; Nour M.; Sindi H.; Moria H.; Rawa M.; Sopian K.; Amin N.; Akhtaruzzaman M. (Elsevier B.V., 2023)
The fabrication of highly efficient nickel oxide (NiOx) thin film for optoelectronic devices is a challenging task because optoelectronic properties are considerably influenced by deposition technique and film thickness. The effect of thickness on the film properties of electron beamphysical vapour-deposited NiOx thin film has been investigated in this work. The influence of post-annealing treatment on the optoelectronic properties of the film was compared with that of the as-deposited one. Optical transparency gradually decreased upon the successive increment in thickness of the as-deposited and annealed films. The surface roughness of as-deposited films increased linearly with the increase in film thickness, but this behaviour was altered in post-annealed films. Spherical grains with high packing density were observed on the as-deposited films, but the grain size was altered substantially on the post-annealed films. The annealed films presented a higher work function than their corresponding as-deposited films. This work presents important insights into the design of photovoltaic devices with an effective deposition process, including a high material utilisation. Moreover, an attempt of fabricating inverted perovskite solar cell on as-deposited and annealing NiOx film as hole transporting material exhibited power conversion efficiency of 11.98% and 12.28%, individually. It was noticed that the high temperature annealing on NiOx film had a very little impact on the comparative photovoltaic performance of aforementioned PSC devices. 2020 The Authors